Bitcoin price forecasting based on historical data - Roy, Shaily; Nanjiba, Samiha (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.